Social Roots of Religion (Review of the 1917-1940 Lithuanian Communist Press) - Mikuckas, Pranas (Problemos, 1975)
The striving of the proletarian atheists to disclose the objective socio-economic factors bringing about religion in society and particularity the analysis of their manifestation in class antagonistic society was a qualitatively new phenomenon in the history of the atheistic thought in Lithuania. The author of the paper traces this process in the 1917-1940 Lithuanian Communist press which was the main loudspeaker of the proletarian atheists in Lithuania. The author shows that by acquiring the Marxist-Leninist methodology of solving one of the main problems of scientific atheism the proletarian atheists of Lithuania went beyond the tradition of the Englishmen on the question of the origin and existence of religion in society, that they propagated the Marxist-Leninist understanding of the social roots of religion and defended it from the opportunist revision by the right social democrats of Lithuania.